2022
DOI: 10.3390/vetsci9010031
|View full text |Cite
|
Sign up to set email alerts
|

European Mistletoe (Viscum album) Extract Is Cytotoxic to Canine High-Grade Astrocytoma Cells In Vitro and Has Additive Effects with Mebendazole

Abstract: Malignant gliomas are associated with extremely poor clinical outcomes in both humans and dogs, and novel therapies are needed. Glioma-bearing canine patients may serve as promising preclinical models for human therapies, including complementary medicine. The objective of this study was to evaluate the effects of mistletoe extract (Viscum album) alone and in combination with mebendazole in an in vitro model of canine high-grade astrocytoma using the cell line SDT-3G. SDT-3G cells were exposed to a range of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Furthermore, veterinary medicine and/or homeopathy are the most promising fields for future applications [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ], not excluding the antiviral properties, which ask for further continuous attention [ 262 ]. Therefore, the knowledge about European mistletoe properties is in continuous evolution and requires a continuous revision of its use in evidence-based complementary and alternative medicine [ 263 , 264 , 265 , 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, veterinary medicine and/or homeopathy are the most promising fields for future applications [ 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ], not excluding the antiviral properties, which ask for further continuous attention [ 262 ]. Therefore, the knowledge about European mistletoe properties is in continuous evolution and requires a continuous revision of its use in evidence-based complementary and alternative medicine [ 263 , 264 , 265 , 266 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of mistletoe extract as a therapeutic agent, its use in conjunction with conventional therapies can achieve a synergistic effect. Therefore, the association between V. album and mebendazole resulted in an increase in cytotoxicity of both compounds in the high-grade canine astrocytoma cell line [44]. Furthermore, the combination of Viscum album preparations with monoclonal antibodies lowers the risk of adverse effects associated with the use of monoclonal antibodies in antitumour therapy [45].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the VAR concentrations tested (ranging from 25 to 200 ug/mL) had no cytotoxic effect on NHDF 36 hours after treatment, enabling the extracts obtained from mistletoe leaves to be tested on the cell proliferation process and the cicatrizing effect. It is known that, at certain concentrations, mistletoe has a cytotoxic effect, that can influence the results of the functional wound healing test (Kuonen et al, 2013;Choi et al, 2022;Wright et al, 2022). Kuonen et al (2013) investigated the effects of mistletoe lipophilic extract and oleanolic acid on the migration of NIH/3T3 fibroblasts as well as HaCat keratinocytes using a wound healing assay, and the results showed that concentrations of mistletoe under 100 µg/mL and oleanolic acid under 12.5 µg/mL were non-toxic to NIH/3T3 fibroblast.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The second stage is the pro-inflammatory stage and is generated by the immune system, where vasodilation occurs and phagocytic cells are focused on cleaning the wound, acting as antimicrobial elements (Antonescu (Mintaș) et al, 2021;Miere et al, 2021;Memete et al, 2023a). VAR extract is a rich source of primary active ingredients consisting of glycoproteins know as mistletoe lectins (ML) and viscotoxins, as well as secondary ingredients such as alkaloids, phenolic acids, flavonoids, phytocompounds that have been shown to have antimicrobial activity and can be considered a stimulator of wound scar formation (Eming et al, 2007;Metelmann et al, 2012;Kleszken et al, 2022bKleszken et al, , 2022aWright et al, 2022).The third phase is based on cell proliferation and wound remodeling. This stage begins with the phenomenon of migration and proliferation of fibroblasts and then the cell matrix and re-epithelialization are formed (Kuonen et al, 2013;Wright et al, 2022;Memete et al, 2023a).…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%